The Gap Symmetry and Fluctuations in High-Tc Superconductors - Bok, Julien.; Deutscher, Guy.; Pavuna, Davor.; Wolf, Stuart A. (NATO Science Series: B, 2002)
Since the discovery in 1986 of high temperature superconductors by J. G. Bednorz and K. A. M©ơller, a considerable progress has been made and several important scientific problems have emerged. Within this NATO Advanced Study Institute our intention was to focus mainly on the controversial topic of the symmetry of the superconducting gap and given the very short coherence length, the role of fluctuations. The Institute on Ớ<U+00dc>The Gap Symmetry and Fluctuations in High- SuperconductorsỚ" took place in the ỚSInstitut dỚ"Etudes Scientifiques de Carg©·seỚ<U+00fd> in Corsica, France, between 1 - 13 September 1997. The 110 participantsfrom 18 countries (yet 30 nationalities) including 23 full time lecturers, have spent two memorable weeks in this charming Mediterranean resort. All lecturers were asked to prepare pedagogical papers to clearly present the central physical idea behind specific model or experiment. The better understanding of physics of high temperature superconductivity is certainly needed to guide the development of applications of these materials in high and weak current devices.